- #1

harpf

- 12

- 0

I'm trying to follow Feynman's explanation on page 9-3 of Volume 3 of The Feynman Lectures on Physics. I've attached a copy of the section in question.

To normalize CII he notes that

< II | II > = < II | 1 >< 1 | II > + < II | 2 >< 2 | II > = 1

I am not clear how he derives the conclusion

CII = 1/√2 (C1 + C2)

I tried to solve the first equation unsuccessfully like this-

< II | 1 >< 1 | II > + < II | 2 >< 2 | II > = 1

CII C1 + CII C2 = 1

[1/√2 (C1 + C2)] C1 + {1/√2 (C1 + C2)} C2 = 1

[1/√2 (C1 + C2)] (C1 + C2) = 1

1/√2 (C1 + C2) (C1 + C2) = 1

which isn’t working for me.

Thank you for clarifying.

To normalize CII he notes that

< II | II > = < II | 1 >< 1 | II > + < II | 2 >< 2 | II > = 1

I am not clear how he derives the conclusion

CII = 1/√2 (C1 + C2)

I tried to solve the first equation unsuccessfully like this-

< II | 1 >< 1 | II > + < II | 2 >< 2 | II > = 1

CII C1 + CII C2 = 1

[1/√2 (C1 + C2)] C1 + {1/√2 (C1 + C2)} C2 = 1

[1/√2 (C1 + C2)] (C1 + C2) = 1

1/√2 (C1 + C2) (C1 + C2) = 1

which isn’t working for me.

Thank you for clarifying.